Strategi Pengembangan Usaha pada Industri Kayu Gergajian Melalui Pendekatan SWOT dan IFAS-EFAS Analysis (Business Development Strategy in Sawn Timber Industry Through the SWOT Approach and IFAS-EFAS Analysis) - Makkarennu Makkarennu; Tri Astuti; Ridwan Ridwan (Masyarakat Peneliti Kayu Indonesia, 2019)
Sawn timber industry is one of the growing timber industries in Indonesia; however, this industry is faced with several problems, including lack of raw materials, product quality, in-efficiency and similar industry competition. The purpose of this study was to determine the quadrant position in the SWOT diagram of sawmill lumber industry and determine the most appropriate strategy in accordance with the position of the quadrant on the SWOT diagram. In-depth interviews method was select to measure strengths; weaknesses, opportunity and threat included senior manager operational and employees of the PT. Madani Cahaya utama. Data were analyzed using SWOT in which the scores of internal factor (Internal Factor Analysis Summary-IFAS) and external factor (External Factor Analysis Summary-EFAS) were calculated. The results showed that score of internal factor and external factor were greater than 2. Hence, the position of SWOT for the small sawmill was located in quadrant 1, suggesting that a company has strength to take an advantage of the existing opportunities.